Automated Online Solid-Phase Extraction Coupled with Sequential Injection-HPLC-EC System for the Determination of Sulfonamides in Shrimp. (25th August 2011) - Chantarateepra, Pimkwan; Siangproh, Weena; Motomizu, Shoji; Chailapakul, Orawon
Abstract : The use of fully automated online solid-phase extraction (SPE) coupled with sequential injection analysis, high-performance liquid chromatography (HPLC), and electrochemical detection (EC) for the separation and determination of sulfonamides has been developed. A homemade microcolumn SPE system coupled with sequential injection analysis (SIA) was used to automate the sample cleanup and extraction of sulfonamides. The optimal flow rate of sample loading and elution was found to be 10  μ L/s, and optimal elution time of zone was 20–24 s. Under the optimal conditions, a linear relationship between peak area and sulfonamide concentrations was obtained in the range of 0.01–8.0  μ g mL −1 . Detection limits for seven sulfonamides were between 1.2 ng mL −1 and 11.2 ng mL −1 . The proposed method has been applied for the determination of sulfonamides in shrimp. Recoveries in the range of 84–107% and relative standard deviations (RSDs) below 6.5% for intraday and 13% for inter-day were received for three concentration levels of spiking. The results showed that the present method was simple, rapid, accurate and highly sensitive for the determination of sulfonamides.